2019
DOI: 10.1007/s40268-019-00286-z
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Oral Immunomodulator Vidofludimus in Patients with Active Rheumatoid Arthritis: Safety Results from the COMPONENT Study

Abstract: Introduction The dihydroorotate dehydrogenase (DHODH) inhibitors leflunomide and teriflunomide are immunomodulatory agents approved to treat rheumatoid arthritis (RA) and multiple sclerosis, respectively, and are actively being investigated as therapeutic agents for other immune-related diseases; however, both structurally related compounds have a number of potentially serious adverse effects. Vidofludimus, a new selective second-generation DHODH inhibitor, is chemically distinct from leflunomide/teriflunomide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…Although there is no strict dose correlation, very high doses of vidofludimus in the phase 1 trials seemed to also result in lowering of serum uric acid levels. Urinary crystallization of uric acid in acidic urine may be speculated to be the event mechanism for these events of hematuria at multiple doses of 70 mg or higher [12]. For this reason, the doses in this trial were selected to not exceed the AUC found in the previous phase 1 trial (SC12267-2-2004) of 70 mg daily repeated SC12267 (AUC 0-24,ss of 259.5 h μg/ml), which led to the findings of hematuria (data on file).…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no strict dose correlation, very high doses of vidofludimus in the phase 1 trials seemed to also result in lowering of serum uric acid levels. Urinary crystallization of uric acid in acidic urine may be speculated to be the event mechanism for these events of hematuria at multiple doses of 70 mg or higher [12]. For this reason, the doses in this trial were selected to not exceed the AUC found in the previous phase 1 trial (SC12267-2-2004) of 70 mg daily repeated SC12267 (AUC 0-24,ss of 259.5 h μg/ml), which led to the findings of hematuria (data on file).…”
Section: Key Pointsmentioning
confidence: 99%
“…Vidofludimus in its form as free acid (lab code: SC12267) using capsules or tablets containing amorphous vidofludimus (previous formulation name: 4SC-101) previously underwent a phase 1 and 2 clinical development program. The clinical efficacy and safety profile of vidofludimus (free acid) were analyzed in clinical studies in healthy volunteers [ 4 ] and patients suffering from rheumatoid arthritis [ 11 , 12 ] and Crohn’s disease and ulcerative colitis [ 4 ]. Single doses up to 350 mg and multiple doses up to 70 mg for 14 days have been tested in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral drug formulation is currently in phase 2 clinical development for autoimmune diseases including multiple sclerosis, ulcerative colitis and primary sclerosing cholangitis. More than 650 individuals have already been treated with IMU-838 or its active moiety, and the safety profile is comparable to the placebo cohort [1][2][3]. Data from the EMPhASIS trial have shown activity of IMU-838 in multiple sclerosis patients who have met the primary and secondary endpoints with high statistical significance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cmp 4 is IM90838 (IMU-838), the Ca 2+ salt of vidofludimus ( Figure 8A), which is currently under testing in phase 2b clinical trials against multiple sclerosis, ulcerative colitis, and primary sclerosing cholangitis. Both vidofludimus and Cmp 4 depend on the same active ingredient in blood (vidofludimus) for their mechanism of action, toxicology, and pharmacology [31].…”
Section: Introductionmentioning
confidence: 99%